An artist’s narrative self-construction: a conversation with Astrid Salles - Santhiago, Ricardo; Salles, Astrid (PORTO ARTE: Revista de Artes Visuais, 2018)
In an interview with Ricardo Santhiago, visual artist Astrid Salles revisits aspects of her formation in the field of artistic creation since her youth in the late 1950s, in the state of São Paulo, in order to review important topics of her life history. She graduated in Music and is recognized as the first woman to play the French horn in Brazil. Astrid worked in illustration and landscape representation and now calls herself a painter. In the conversation, she recounts, among other points, her encounter with sertanist Orlando Villas-Bôas, which was crucial for her to dedicate her visual art production to reinterpreting indigenous graphic patterns.